Association between global biomarker of oxidative stress and quantitative ultrasound parameters in middle-aged and elderly adults: A cross-sectional study - Shen, Xue; Liu, Yawen; Zhao, Qianqian; Cheng, Haitao; Li, Binbin; Vuong, Ann M.; Fan, Yiliang; Zhang, Mengmeng; Yang, Shuman (Frontiers in Public Health, 2023)
Introduction With the population aging, osteoporosis has become a major public health concern. Elevated oxidative stress is a vital detrimental factor for bone health. Compared to common oxidative stress-related biomarkers, Fluorescent Oxidation Products (FlOPs) reflect the global levels of oxidation from proteins, lipids, and DNA. Nevertheless, whether plasma FlOP levels are related to bone health measured by Quantitative ultrasound (QUS) is unclear. Thus, the present study examined the association between FlOPs and QUS parameters in middle-aged and elderly adults. Methods This community-based cross-sectional study was conducted in Changchun, northeast China. Plasma FlOPs were determined by a fluorescent microplate reader at a wavelength of 320/420 nm (excitation/emission). QUS parameters [speed of sound (SOS) and broadband ultrasound attenuation (BUA)] of the calcaneus were assessed by an ultrasound bone densitometer. We used multivariable linear regression to examine the association between FlOPs and QUS parameters. Results A total of 491 subjects were included in this study. Their average age was 65.2 years (standard deviation [SD]: 9.7 years). FlOPs were inversely associated with SOS (β for an increase of logarithmic interquartile range = −10.64; P = 0.018). Higher FlOP levels were marginally associated with lower SOS in females (β for an increase of logarithmic interquartile range = −9.68, P = 0.066), but not in males (β for an increase of logarithmic interquartile range = −11.84, P = 0.131). No significant relationship between FlOPs and BUA was observed. Conclusions Plasma FlOP levels were inversely associated with SOS, but not with BUA in middle-aged and elderly adults.